Shariah compliant hibah product: a study at As-Salihin Trustee Berhad / Nur Shakirah Mohd Samsol Anuar - Mohd Samsol Anuar, Nur Shakirah (2019)
Early planning of the distribution of property was crucial for Muslims in avoiding the problems that would arise with the property left behind after their death as an example of unclaimed property in Malaysia. In sequence, hibah is seen as an alternative to Islamic wealth management. Hibah needs to understand in-depth; in terms of the concept, application, and procedures. This paper focuses on the practice of hibah product offered by As-Salihin Trustee Berhad. This research employed the qualitative method to accomplish the objectives. It is found that hibah product offered by As-Salihin Trustee Berhad is one of the flexible and faster instruments in wealth distribution and give benefits for the Muslims. Besides that, As-Salihin also has through challenges in the management of the hibah product offered likes the property cannot pass to the beneficiary occured from the unpaid payment. It is hoped that more Muslim society will select hibah in the future as one of the wealth planning instruments due to its benefits and privileges.